Occurrence, risk factors and antimicrobial resistance of Campylobacter from poultry and humans in central Ethiopia: A one health approach. - Fikre Zeru; Haileeyesus Adamu; Yohannes Hagos Woldearegay; Tesfaye Sisay Tessema; Ingrid Hansson; Sofia Boqvist (PLoS Neglected Tropical Diseases)
Background Campylobacter is a leading foodborne pathogen posing a significant One Health challenge due to broad animal reservoirs and serious antibiotic resistance. Despite frequent human-animal-environment interactions in Ethiopia, One Health studies on Campylobacter occurrence and transmission are crucial but lacking. Methodology/principal findings A cross-sectional study was conducted from March 2021 to March 2022 in central Ethiopia using a One Health approach to assess Campylobacter occurrence and resistance in humans, poultry and environment, and identify risk factors in humans and poultry. A total of 366 samples from 122 poultry farms were collected, including cloacal swabs, human stools, and poultry house floor samples. Epidemiological data on risk factors and respondents' awareness were gathered through interviews. Campylobacter spp. were isolated following ISO 10272, confirmed with multiplex PCR and tested for antimicrobial susceptibility using the disc diffusion method according EUCAST guidelines. Campylobacter spp. were detected in 12.5% samples, highest in poultry (19.6%), followed by humans (13.1%) and poultry house floor (4.9%). Campylobacter jejuni was the dominant species (80.4%), followed by C. coli (19.6%). In poultry, mixed farming with cattle increased Campylobacter colonization odds (adjusted odds ratio; AOR = 9.5), while all-in/all-out management decreased it (AOR = 8.4). In humans, Campylobacter infection was linked to raw milk consumption (AOR = 5.5), poultry access to living areas (AOR = 6.3), not using personal protective equipment when working with poultry (AOR = 8.3) and not washing hands after handling poultry and cleaning barn (AOR = 5.6). Farm workers had a knowledge gap in zoonotic risks, including Campylobacter and One Health. High antibiotic resistance was observed, especially to erythromycin (63.0%), ciprofloxacin (69.5%), tetracycline (89.1%), and oxytetracycline (73.9%), with 69.5% of isolates showing multidrug resistance. Conclusions/significance The study revealed widespread occurrence of resistant Campylobacter spp. in poultry, workers, and the environment, highlighting the need for One Health interventions: improved biosecurity, hygiene, education, and responsible antimicrobial use to safeguard animal and human health.